EEG/MEG-Quellenrekonstruktion bei nichtläsioneller Epilepsie - Heide, Ev Christin; Rampp, Stefan; van de Velden, Daniel; Seeck, Margitta; Focke, Niels K. (Clinical Epileptology, 2023)
Background: The postsurgical outcome of non-lesional epilepsy is worse compared to that of lesional epilepsy. Electric and magnetic source imaging (ESI/MSI) are very important methods for the presurgical identification of the epileptogenic focus. Objective: The aim of this article is to provide an overview on the current state of knowledge on ESI and MSI in non-lesional epilepsy. Material and methods: The article presents a non-systematic literature review. Results and conclusion: Source imaging has proven its usefulness in the localization of the epileptogenic focus in non-lesional epilepsy patients. The concordance of the resection zone or intracranial EEG and the source imaging in patients with a good surgical outcome was high. It provides non-redundant information in a relevant proportion of patients by identifying unknown lesions; however, only 9 of 25 surveyed European epilepsy centers reported using ESI in their presurgical evaluation. Semi-automated source reconstruction and limitation of the number of spikes and electrodes needed could help to improve its practicability and increase its use in epilepsy centers.
CRIS-Team Scopus Importer:2023-05-26
Keywords: Electroencephalography; Magnetoencephalography; Non-lesional epilepsy; Presurgical evaluation; Source reconstruction